Exploring the Nanomedicinal Features of Ayurvedic Bhasmas: Insights from Traditional Medicine - Bimal, Rajchal; Pramod, Bhatta; Rameshwar, Adhikari (International Journal of Complementary Medicine, 2025)
Ayurveda is a traditional and scholarly medical system practiced in South Asia since the Vedic period. It integrates science and philosophy to promote a healthy, happy and prosperous life. Ayurvedicbhasmas are classical formulations that contain non-toxic forms of metals and minerals, enriched with therapeutic metabolites. These bhasmas are produced through repeated trituration of metals and minerals with the extracts from potent Ayurvedic herbs, followed by intense heating at temperatures above 650 °C. The preparation process of bhasmas closely resemble top-down approach in nanoparticle synthesis, resulting in very fine calcined nano-powders. These powders are used effectively in Ayurvedic treatments for various ailments, particularly chronic diseases. Recent studies have highlighted that bhasmas possess antioxidant, anti-inflammatory, antibacterial, antiviral and antitumor properties and may serve as potential carriers for drug delivery. This paper aims to compare bhasma particles prepared by traditional and modern methods, explore the therapeutic benefits of different bhasmas, and investigate the nanomedicinal features of various Ayurvedicbhasmas.
Keywords: Ayurveda; Ayurvedic Formulations; Nano-powders; Nanomedicine; Traditional medicine; Vedic medicine